Super-hygroscopic film for wearables with dual functions of expediting sweat evaporation and energy harvesting. (September 2020) - Zhang, Xueping; Yang, Jiachen; Borayek, Ramadan; Qu, Hao; Nandakumar, Dilip Krishna; Zhang, Qian; Ding, Jun; Tan, Swee Ching
Abstract: Despite the boom in atmospheric water-harvesting techniques, few attempts have been made with a broader horizon–absorbing the moisture from sweatevaporation, which has substantial implications for human comfort and wearable electronics. Herein, a cobalt-complex-based super-hygroscopic material (Co-SHM) is developed to expedite sweat evaporation and fabricate moisture-triggered energy harvesting devices. The Co-SHM features transparent thin-film structure, fast absorption kinetics and high water uptake of 4.6 g g −1 . The material regeneration can be driven by natural sunlight, making the Co-SHM an energy-efficient moisture absorbent. Integrating the Co-SHM into breathable and waterproof PTFE membranes, we design new kinds of armpit pad, shoe lining, and insole, which can rapidly absorb the moisture from sweat to prevent sweat accumulation, thereby providing a dry and comfortable microclimate for people. Furthermore, the absorbed sweat can be transduced to energy through a Co-SHM based wearable energy harvesting devices. The harvested energy can power a light-emitting diode. This work holds significant economic potential in the fields of functional clothing, footwear, and wearable electronics. Graphical abstract: A cobalt-complex-based super-hygroscopic material (Co-SHM) that can rapidly and reversibly absorb moisture while using the natural sunlight for material regeneration has been developed. Integrating the Co-SHM into wearables can expedite sweat evaporation and construct wearable energy harvesting device. Image 1 Highlights: A cobalt-complex-based super-hygroscopic material (Co-SHM) featuring solar-driven regeneration is prepared. Integrating the Co-SHM into wearables can rapidly absorb moisture from sweat evaporation. A wearable energy harvesting device is fabricated to transduce the absorbed sweat into energy.